2018
DOI: 10.3390/w10101315
|View full text |Cite
|
Sign up to set email alerts
|

Developing an EFDC and Numerical Source-Apportionment Model for Nitrogen and Phosphorus Contribution Analysis in a Lake Basin

Abstract: The numerical source-apportionment model is an efficient and useful method for analyzing water-quality responses to nutrient loading in rivers and lakes. In this study, the Environmental Fluid Dynamic Code (EFDC) and numerical source-apportionment model were applied to Lake Bali in Jiujiang City, China to predict the contributions of various pollution sources to the lake at any time and position. We calibrated and validated the model by comparing its predictions with observed hydrodynamic and water-quality par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…We showed that the 3D model EFDC was able to simulate stratification dynamics in Lake Arendsee with high precision, resulting in an overall RMSE of only 0.78 K between modelled and observed water temperatures. The errors in our study were much lower than those presented in recent studies in which EFDC was applied (Bai et al, ; Zheng et al, ). The RMSE was different between layers and generally lower within the hypolimnion towards the lake bottom, which is related to lower temperature variations in this region (Figure ).…”
Section: Discussioncontrasting
confidence: 75%
“…We showed that the 3D model EFDC was able to simulate stratification dynamics in Lake Arendsee with high precision, resulting in an overall RMSE of only 0.78 K between modelled and observed water temperatures. The errors in our study were much lower than those presented in recent studies in which EFDC was applied (Bai et al, ; Zheng et al, ). The RMSE was different between layers and generally lower within the hypolimnion towards the lake bottom, which is related to lower temperature variations in this region (Figure ).…”
Section: Discussioncontrasting
confidence: 75%
“…Recently, many researchers tried to couple the EFDC model with other watershed models in order to identify the effects of nonpoint source pollution [14,28,29]. In addition to that, in this study we also considered the pollutants derived from anthropogenic activities such as cage farming and damming in the tributary with the coupled model.…”
Section: Discussionmentioning
confidence: 99%
“…Implicit Crank Nicolson scheme has been used in approximating the advection diffusion equation. Bai et al, 2018, presented effective on the optimization of pollution load reduction in the lake and can be utilized to evaluate the most useful implementation of its pollution-control plan. Results are used to forecast the transportation of water pollution concentration by employing the velocity and diffusion parameters.…”
Section: Pollutant Transport and Resultsmentioning
confidence: 99%